Implementation of independent leg muscle training aids using Wemos D1 mini - Agus Hariyanto; Bekti Maryuni Susanto (Compiler, 2022)
Badminton is a game that uses a shuttlecock as a tool which is played by hitting it with a racket. One form of exercise that is most often applied in training leg muscle strength is shadow training. This exercise aims to simulate athletes to do footwork properly and correctly. Shadow training is an exercise to train leg muscle strength and leg agility. Usually athletes when training leg muscles and leg agility use shadow exercises manually, namely by moving the shuttlecock or cone from one side to the other with instructions from the trainer. client and server applications. The connection between the client application and the server application uses a wifi network. The server application can control the light on the client application. There were tests by players on the badminton court which were carried out as many as 20 trials with a time of 30 seconds for each trial; the results obtained with the sequential method obtained an average of 5.84 muscle exercises, with the random method obtained an average of 5.9 times muscle training, with the method determined by the system the average time was 30.12 seconds.